Winter Maintenance of Permeable Interlocking Concrete Pavement: Evaluating Opportunities to Reduce Road Salt Pollution and Improve Winter Safety. Issue 2 (February 2021) - Marvin, Jeffrey T.; Scott, Jody; Van Seters, Tim; Bowers, Robert; Drake, Jennifer Anne
Permeable interlocking concrete pavement (PICP) is a type of permeable pavement system that uses the joint spaces between pavers to drain water from the surface into an aggregate base and subbase layer below. Because of its ability to rapidly drain surface water, PICP has the potential to reduce the amount of ice formed on the surface during winter conditions compared with traditional impervious pavements. As a result, PICP may reduce the amount of road salt needed for de-icing paved surfaces and may also reduce the risk of pedestrian slipping and vehicle skidding throughout the winter. This study evaluates the performance of an outdoor PICP and asphalt test pad over two winter seasons in Vaughan, Ontario, Canada, by assessing differences in surface conditions, surface friction, and surface temperatures. The results of this study indicate that PICP provides equivalent or higher levels of safety compared with asphalt when treated with de-icing products at medium (0.049 kg/m 2 ) or low (0.024 kg/m 2 ) application rates. Re-freezing of melted snow and ice after sunset was observed on the asphalt surface creating black ice, but not on the PICP cells. Consequently, compared with asphalt pavements, PICP surfaces will require use of less de-icer and will have lower risk of slips and falls for pedestrians, and lower risk of skidding for vehicles throughout the winter.